(untitled) (Applied Biological Research, 2022)
The presentstudy was aimedto assessthe effects of direct current (DC) on inducing the stage-IV anaesthesia in Nile tilapia (Oreochromis niloticus). Underwater DC of different magnitudes viz., 30, 60, 90 and 200 V applied for 25 sec in all, except 200 V whereinexposure time varied from 15 to 30 sec. Notably, the exposure to 30, 60, and 90 V for 25 sec did not induce anaesthesia; while 200 V DC lead to successful anaesthesia. Opercular movements in fishes exposed to 200 V after 1 min of recovery was significantly higher than before exposure value. Opercular movements sloweddown gradually; and after 15 min of recovery no significant difference in opercular movement was observed. Normal swimming activity and reactivity to tactile stimuli were restored after 10 min of recovery. The results suggest that DC at 200 V was effective in inducing anaesthesia in O niloticus with fast induction (15-30 sec) and recovery period (20-55 sec). This revealed that the electro-anaesthesia technique used in this study offer a cost-effective, safe and eco-friendly alternative of chemical anaesthetics.